Managing hydrogen bonding in the clathrate hydrate of the 1-pentanol guest molecule. Issue 26 (21st June 2021) - Lee, Byeonggwan; Kim, Jeongtak; Shin, Kyuchul; Park, Ki Hun; Cha, Minjun; Alavi, Saman; Ripmeester, John A.
Abstract : 1-pentanol, long-chain alcohol molecule, can be encaged in the clathrate hydrate by managing the destabilizing influence of guest–host hydrogen bonding. Abstract : It remains a difficult task to predict the hydrate structure and conformation of potential guest molecules in one of the three canonical hydrate lattices. 1-Pentanol is characteristic of molecules that lie at the margin of suitability as a guest molecule for the structure II hydrate phase, both because of its size and the presence of a hydrophilic OH group that tends to destabilize the clathrate hydrate framework. To manage the destabilizing influence of guest–host hydrogen bonding, some years ago a more robust framework was developed by doping the hydrate with NH4 + and F − ions in order to direct the guest hydrophilic groups away from the cage water molecules. Attempts to enclathrate 1-pentanol in the NH4 F doped clathrate were successful, but, surprisingly, the clathrate, as determined by PXRD, proved to be structure II (sII), even though the 1-pentanol appears to be too large to fit the pseudo-spherical 5 12 6 4 cage. This suggested that the doped clathrate not only managed the guest–host hydrogen bonding network, but also forced the guest into a very compact conformation to fit the pseudospherical sII large cage (5 12 6 4 ). These features were investigated further with 13 C NMR and molecular dynamics simulations to identify the most likely guest conformation of 1-pentanol in the sII large cage.